2018
DOI: 10.1007/s13311-018-0606-7
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Nanocurcumin as Add-On Therapy to Riluzole in Patients With Amyotrophic Lateral Sclerosis: A Pilot Randomized Clinical Trial

Abstract: The objective of present study was to assess the safety and efficacy of nanocurcumin as an anti-inflammatory and antioxidant agent in adults with amyotrophic lateral sclerosis (ALS). We conducted a 12-month, double-blind, randomized, placebo-controlled trial at a neurological referral center in Iran. Eligible patients with a definite or probable ALS diagnosis were randomly assigned to receive either nanocurcumin (80 mg daily) or placebo in a 1:1 ratio. A computerized random number generator was used to prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 44 publications
(44 reference statements)
1
83
0
Order By: Relevance
“…No significant difference was observed in ALSFRS-R score, muscle strength, and CMAP amplitude decrements between the nano-curcumin and placebo groups. 94…”
Section: Application Of Nano-curcumin In Clinical Trialsmentioning
confidence: 99%
“…No significant difference was observed in ALSFRS-R score, muscle strength, and CMAP amplitude decrements between the nano-curcumin and placebo groups. 94…”
Section: Application Of Nano-curcumin In Clinical Trialsmentioning
confidence: 99%
“…A possible component involved in the nanocurcumin failure in this randomized trial is the duration of its pretreatment before the RT course initiation. Recently, several clinical trials on SinaCurcumin® have had favorable results for the clinical application of curcumin after long‐term administration (Ahmadi et al, ; Alizadeh et al, ; Dolati, Aghebati‐Maleki, et al, ). Based on these randomized trials, we assumed that a longer duration of supplementation seems to produce a better outcome.…”
Section: Discussionmentioning
confidence: 99%
“…SinaCurcumin® as a novel nanoformulation of curcuminoids has recently demonstrated considerable efficacy in different clinical settings. Some favorable results have been shown in patients with amyotrophic lateral sclerosis, multiple sclerosis, ulcerative colitis, HTLV‐1 associated myelopathy/tropical spastic paraparesis (HAM/TSP), type 2 diabetes, nonalcoholic fatty liver disease, and as well as infertile patients (Ahmadi et al, ; Alizadeh et al, ; Dolati, Aghebati‐Maleki, et al, ; Dolati, Ahmadi, et al, ; Jazayeri‐Tehrani et al, ; Masoodi et al, ; Mohammadi et al, ; Rahimi et al, ). The main underlying mechanisms included the modulation of some inflammatory factors, posttranscriptional activities, and total antioxidant capacity (Alizadeh et al, ; Dolati, Aghebati‐Maleki, et al, ; Dolati, Ahmadi, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It binds to the pre-fibrillar aggregates of SOD1, altering its amyloidogenic pathway and decreasing cytotoxicity (Bhatia et al, 2015). Curcumin may improve survival in patients with ALS, especially those with bulbar involvement (Ahmadi et al, 2018). In a double-blind therapeutic trial, treatment with curcumin showed a decrease in ALS progression and a reduction of oxidative damage (Chico et al, 2018) (Table 1).…”
Section: Curcuminmentioning
confidence: 99%